1993
DOI: 10.1038/bjc.1993.372
|View full text |Cite
|
Sign up to set email alerts
|

Haematological toxicity of carboplatin and cisplatin combined with whole body hyperthermia in rats

Abstract: Summary Acute haematological toxicity induced by cis-diammine-1,1-cyclobutane dicarboxylate platinum (II) (carboplatin) and cis-diamminedichloroplatinum (II) (cisplatin) in combination with whole body hyperthermia (WBH) (2 h at 41.5°C) was examined using a F344 rat model. The thermal enhancement ratios (TERs) of drug-mediated thrombocytopenia, anaemia and leukopenia were determined from the dose-response curves of the nadir values of the peripheral platelet, RBC and WBC counts. Carboplatin produced profound de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…(Siddik et al, 1987). The data on carboplatin-induced anaemia obtained in the present study are in good accordance with observations made by other investigators (Siddik et al, 1987;Ohno et al, 1993), describing a dose-dependent induction of anaemia with carboplatin doses between 40 and 60 mg kg-'. Although Siddik et al (1987) concluded that internal haemorrhaging as a result of thrombocytopenia causes the carboplatin-induced anaemia, no signs of severe bleeding were observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…(Siddik et al, 1987). The data on carboplatin-induced anaemia obtained in the present study are in good accordance with observations made by other investigators (Siddik et al, 1987;Ohno et al, 1993), describing a dose-dependent induction of anaemia with carboplatin doses between 40 and 60 mg kg-'. Although Siddik et al (1987) concluded that internal haemorrhaging as a result of thrombocytopenia causes the carboplatin-induced anaemia, no signs of severe bleeding were observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, decreased TEC and Hb by cisplatin may be the attributing factor for decreased level of PCV in present study. Mild thrombocytopenia is one of the consequences of hematological toxicities by cisplatin 16 , however; the observations in the present study are not in agreement with above report. This might be due to reversible appearance of thrombocytes to the normal levels by 18 days or inability of cisplatin to suppress platelets at dose (7.5 mg/kg) used in present study.…”
contrasting
confidence: 55%
“…Previous work by others has evaluated whole body hyperthermia (WBH) protocols in which the patient is brought to relatively hot systemic temperatures (e.g. greater than 41.5 C) in combination with various chemotherapeutic agents [30][31]; however, clinical gain was limited by increased chemotherapy-induced toxicity [32]. As a result, Bull and co-workers pioneered a milder (i.e.…”
Section: Introductionmentioning
confidence: 99%